Cancer-related anaemia - Gawrychowski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2006)
Cancer-related anaemia occurs during the underlying malignancy in 40-75 percent of the patients. It has the influence on the quality of life, which can be significantly reduced and on the results of the planned and undergoing treatment. The mild anaemia can negatively impact the therapeutic treatment. Anaemia is often exacerbated by cancer treatment- -chemotherapy and radiotherapy. The blood transfusions or erythropoietin therapy help to equalize the decreased level of haemoglobin. Particular attention must be paid to the patients who received myelosuppressive treatment, radiation (in the pelvis minor area) and in cases when after the first course of chemotherapy the level of haemoglobin decreased by 2 g/dl. Numerous clinical studies have shown that erythropoietin can be an effective treatment in cancer-related anaemia.